Genetic diversity of natural Silver fir populations in Bulgaria - Ivan Evtimov; Fritz Bergmann; Petar Zhelev (Silva Balcanica, 2024)
Genetic diversity of eleven natural populations of Silver Fir in Bulgaria was studied by means of allozyme gene markers. Within population diversity varied among populations and was generally high, but within the range reported for other European populations of the species. Mean number of alleles per locus ranged from 2.1 to 2.4 and effective allele number – from 1.2 to 1.5. Expected and observed heterozygo-sities were also high (mean values 0.295 and 0.265, respectively), but there was significant heterozygote deficiency in most loci and populations, resulting in positive inbreeding coefficient (mean FIS=0.049). Differentiation among populations was low (FST = 0.027), resulting probably from extensive gene flow and recent divergence. The results are discussed in the light of conservation and sustainable management of Silver Fir natural populations.